Compulsory female sterilisation in Brazil: reproductive rights for whom? - Menandro, Leila Marchezi Tavares; Barrett, Hazel Rose (Critical and radical social work, 2022)
Family planning programmes have been implemented throughout the world since the mid-20th century. In Brazil, the act governing family planning has been law for 25 years. However, the concept does not seem to be well known, being understood as contraceptives distribution. This article discusses Brazilian family planning policies, using a compulsory sterilisation lawsuit – reported by the media – to illustrate one of the many facets of gender-based violence in Brazil. This article is based on documentary research and uses a qualitative approach, applying content analysis to three selected texts. Only the news report that made the case public directly mentions the Family Planning Law and questions the suppression of reproductive rights. It was clear that conservatism was present in the actions of the judiciary, which appeared to be selective when choosing whose rights should be protected, denying poor women’s reproductive rights and upholding coercive birth control for the most deprived groups in the population.